2007
DOI: 10.4067/s0365-28072007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insecticide Activity of Two Agricultural Detergents against the Long-Tailed Mealybug, Pseudococcus longispinus (Hemiptera: Pseudococcidae), in the Laboratory

Abstract: The insecticide effect of agricultural detergents SU 120 and Tecsa Fruta was evaluated on females and nymphs II of Pseudococcus longispinus (Targioni & Tozzetti) in the laboratory. Mortality at 24 h was subjected to Probit analysis to obtain the LC 50 . For Tecsa Fruta, a volume of 9.5 mL solution was sprayed, while for SU 120, volumes of 2, 4, and 8 mL 100 mL -1 solution were evaluated. Mortality was directly related to the concentration used. Nymphs II were more susceptible than females to both detergents. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Surfactants have lately also been considered as less human-toxic and cheaper alternatives to conventional insecticides in agriculture (Oetting & Latimer 1995;Curkovic et al 2007). Their activity has been attributed to several factors, such as drowning pest insects, destroying biological membranes, inhibiting enzymes or simply removing individuals from the foliage (Curkovic & Araya 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Surfactants have lately also been considered as less human-toxic and cheaper alternatives to conventional insecticides in agriculture (Oetting & Latimer 1995;Curkovic et al 2007). Their activity has been attributed to several factors, such as drowning pest insects, destroying biological membranes, inhibiting enzymes or simply removing individuals from the foliage (Curkovic & Araya 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The detergent used at 1% v/v kept the solution neutral, but it might affect the pH solution when detergent is used at greater concentrations (Villar 2015). Previous experience on mobile stages of mealybugs exposed to detergent treatments indicates that the stage in which they are more easily controlled by detergent solutions corresponds to first instar nymph (Curkovic et al, 2007). However, first instar nymphs were by far the most frequent stage in which they were found alive in the present study (Table 2); individuals were mainly found walking on the fruit surface or inside the calyx cavity after treatments and cold storage.…”
Section: Discussionmentioning
confidence: 44%
“…Insecticidal soaps disrupt the waxy cuticle or "skin" of the insect, which eventually causes the insect to dry out (desiccate) and die. Nirma powder with neem oil in the control of long tailed mealy bug was reported by 17 . The above reports support the present work.…”
Section: Resultsmentioning
confidence: 99%